Mobilidade e acessibilidade urbana: o ir e vir por meio do transporte público coletivo - Poletto, Pollyana (2016)
Through this research we seek to verify the conditions of urban mobility and accessibility of the population of Pato Branco-PR city. As a result, we selected for the research the most democratic means of displacement available in the city, the Collective Public Transportation (CPT). However, to analyze the conditions of urban mobility and accessibility, it is first necessary to consider the structuring and expansion of urban space, because, the individual's area of residence directly influences the quality of their mobility and access to urban facilities. In the city study, urban expansion occurred more intensely in the South and Southwest portions, which were set up in residential areas for the segments of lower purchasing power, further stimulating the establishment of sub-centers and commercial services. The presence of these sub-centers is beneficial to society as a whole, as well as urban equipment to decentralize-spreading up the various areas of the city, which facilitates the access of the population. However, despite the decentralization of urban equipment, trips to the center are still very significant, because it is the center that there is diverse range of products and services beyond the prices are more attractive. Thus, the shifts have been expanded as well as the option for private car over public transport. This is because the facilities in the purchase of cars and motorcycles, and more decisively due to the CPT system lag. This change in people's behavior (encouraged by the lack of Government investment in the transport sector) has caused significant congestion on city roads, causing increased pollution and "immobility" of the population. In order to understand the real reasons of this whole problem, we elaborated steps to the research, using many references in order to base the analyzes and reflections, we conducted fieldwork for information on the means of transport studied, and for better understanding, we interviewed users and non-users of the CPT, as well as representatives of the government (Institute for Research and Planning of Pato Branco - IPPUPB and DMV - DEPATRAN) and business (LP Transport Collective and Transangelo Transport Collective LTDA) that proffer this service. The interviews were essential to know the real needs of users and obtain information on: conditions of vehicles, buildings, points of embarkation / disembarkation, setting the lines and routes, timing, rate, exemptions and discounts, integration, popular participation in moments of this displacement means planning and forecasting of the Government's actions and businessmen to improve the service. Finally, we seek to contribute to the improvement of CPT suggesting proposals, which will then be forwarded to the Government and businesses, so that they can be taken into account at the time of the urban space planning, as well as the displacement means used bypopulation. We believe that only in this way, the right to come and go can be accomplished, which is the key factor to ensure the right to the city, that even being highlighted in separate laws is very little implemented.